Ação da fotobiomodulação (670nm) isolada ou associado a vitamina A e ácido carboxietil gama aminobutírico (CEGABA) no processo de reparo tecidual de feridas em ratos - Otterço, Albaiza Nicoletti (Universidade Federal de São Carlos, 2018)
Photobiomodulation (FBM) has been indicated in cases of tissue repair due to characteristics such as: stimulation of fibroblast proliferation, reduction of the inflammatory process, and acceleration of collagen synthesis. The objective of the present study was to evaluate the application of the 670 nm laser isolated and associated with the vitamin A and carboxyethyl gamma aminobutyric acid (CEGABA) in the treatment of wounds on the back. This study was approved by the Animal Ethics Committee of UFSCar. 60 male Wistar rats were divided into 6 groups (n = 10), with Control (CG); Laser (LG); GaAlAs 670nm continuous pulse, 30mW power, energy density 14.28J/cm2, irradiating 1 spot per wound for 30s; Vitamin A (VitAG) on a high hydrolipidic basis; CEGABA (CgG) 1% CEGABA/volume on a high hydrolipidic basis; Laser + Vitamin A (LVitAG) Laser + CEGABA (LCgG). Three wounds of 10mm diameter were induced by dermatological punch on the animal's back. The treatment totaled 15 consecutive days. Samples were collected on the 4th, 11th and 16th day for histological analysis of HE, Picrosirius-Red, immunohistochemistry (COX-2, TNF-α, VEGF and collagen I). For the statistical analyzes, the one-way and two-way ANOVA test were used for the intra and inter-group evaluations, respectively, and the Tukey and Bonferroni post-test. The level of significance was 5%. The results for the histopathological analysis showed a statistically significant difference for lower values of inflammatory infiltrate in LG versus GG on the 16th day; in LG versus CG and VitAG on the 4th day; and for the increase of collagen in LG versus CG on the 11th and 16th days of treatment. There was a statistically significant difference for the increase of VEGF on the 4th and 11th day for LG and L+VitAG when compared to the other groups. Decrease of TNF-α on the 4th and 11th day for LG and increase of collagen type 1 on the 4th and 16th days in LG when compared to the other groups. The birefringence analysis was a statistically significant difference for increase of collagen fibers on the 11th day for LG when compared to the other groups. In view of the presented results, it is pertinent to point out that FBM is effective in helping the kinetics of the cutaneous wound healing process in rats and promoted the necessary stimuli so that the healing process evolved with quality and in a satisfactory way, tissue considered structurally desirable
Action of photobiomodulation (670nm) isolated or associated with vitamin A and carboxyethyl gamma aminobutyric acid (CEGABA) in the tissue repair process of wounds in rats
Keywords: Fotobiomodulação; Laser 670nm; Vitamina A; Ácido carboxietil gama aminobutírico; Ferida de pele; Reparo tecidual; Carboxyethyl aminobutyric acid; Wound skin; Photobiomodulation; Tissue repair; Vitamin A; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL